The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s0100-204x2016000500025
|View full text |Cite
|
Sign up to set email alerts
|

Sowing date reduces the incidence of wheat blast disease

Abstract: -The objective of this work was to assess the effect of sowing date on the intensity of wheat blast disease, as well as the yield losses caused by this disease in different wheat (Triticum aestivum) genotypes. The experiments were conducted in 2013 at the Sertãozinho experimental station of Empresa de Pesquisa Agropecuária de Minas Gerais (Epamig), in the municipality of Patos de Minas, in the state of Minas Gerais, Brazil. Fourteen wheat genotypes and two sowing dates were evaluated. The experimental design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 21 publications
3
22
1
Order By: Relevance
“…In this study, 1,106 lines in the IBWSNs and SAWSNs were evaluated for wheat blast in Bolivia and Bangladesh, and we observed a high level of resistance, with 83.7% of them having mean blast indices less than 10. In the environments considered in this study, the planting time did not significantly affect the disease indices except in one dataset, in contrast to a previous observation 29 . In addition, traits like days to heading and height had low correlations with disease index which can be partly attributed to the low variability in the blast indices.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, 1,106 lines in the IBWSNs and SAWSNs were evaluated for wheat blast in Bolivia and Bangladesh, and we observed a high level of resistance, with 83.7% of them having mean blast indices less than 10. In the environments considered in this study, the planting time did not significantly affect the disease indices except in one dataset, in contrast to a previous observation 29 . In addition, traits like days to heading and height had low correlations with disease index which can be partly attributed to the low variability in the blast indices.…”
Section: Discussioncontrasting
confidence: 99%
“…Management of wheat blast using fungicides is possible, but has been reported to be elusive, because of the inefficiency of fungicides in offering complete control under high disease pressure, the resistance in MoT populations to some classes of fungicides, and the high cost of the fungicides that cannot be afforded by resource-poor farmers 4 , 6 , 9 , 26 28 . While other potential blast control measures including altering the sowing time 5 , 29 , suspending the cultivation of wheat in disease-prone areas and declaring a ‘wheat holiday’ will help to mitigate the disease spread to some extent, the development and deployment of wheat varieties with genetic resistance to blast has been resorted to as the most sustainable and farmer-friendly approach 4 , 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also showed that blast disease negatively affects the variables linked to wheat physiology and, consequently, grain yield, particularly during early grain filling (Rios et al, 2017). Under field conditions, significant correlations were observed between disease index and yield losses (Coelho et al, 2016). In Argentina, four commonly used wheat cultivars were evaluated after inoculation of eight M .…”
Section: Discussionmentioning
confidence: 99%
“…In South‐East Asia, jute ( Corchorus olitorius ) cultivation could be an option for crop rotation (Government of India, ). Altering the sowing date to prevent an overlap between flowering or grain filling stages and blast‐conducive periods characterized by high temperatures, rain and high relative humidity is an effective cultural practice to manage wheat blast in South America (Coelho et al ., ; Mehta, ; Mehta et al ., ). Field experiments designed to dissect the epidemiology of wheat blast will be needed to determine which of these strategies will have the greatest impact.…”
Section: Strategies For the Management Of Wheat Blastmentioning
confidence: 99%